Antimicrobial Activity of 5-membered Nitroheteroaromatic Compounds beyond Nitrofurans and Nitroimidazoles: Recent Progress - Kalinin, Stanislav; Vedekhina, Tatiana; Paramonova, Polina; Krasavin, Mikhail (Current Medicinal Chemistry, 2021)
The last decade has been characterized by the development and approval of pretomanid and delamanid, which are nitroimidazole based drugs for multidrug -resistant tuberculosis. This attracted renewed attention to the nitroheterocyclic scaffolds as a source of safe and efficient antimicrobial agents. While the primary focus is still on nitrofurans and nitroimidazoles, well known as bioreducible prodrugs, a number of studies have been published on other 5-membered nitroheteroaromatic compounds. The latter not only show promising antimicrobial activity but also demonstrate modes of action different from the conventional reductive activation of the nitro group. Considering the potential of these efforts to impact the continuing race against drug-resistant pathogens, herein we review non-furan/imidazole-based 5-membered nitroheteroaromatics investigated as antimicrobial agents in 2010-2020.
Keywords: drug-resistant pathogens